2010
DOI: 10.1007/s12253-010-9332-0
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Twist in Gastric Carcinoma Associated with Tumor Invasion and Poor Prognosis

Abstract: Tumor invasion and metastasis are the most common causes of death in gastric carcinoma. Twist, a transcription factor of the basic helix-loop-helix class, reportedly regulates cancer metastasis and induces epithelial-mesenchymal transition (EMT). We evaluated the expression of Twist and its effect on cell migration in gastric carcinoma (GC). Twist expression was detected by real-time quantitative RT-PCR in gastric tumor tissue, metastatic lymph nodes and normal gastric tissue from 47 gastric carcinoma patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…During EMT, gastric cancer cells with fibroblastic morphologic changes show increased migration and invasiveness as a result of decreased cell-cell adhesion, and the cells then acquire a spindle-shaped, highly motile fibroblast phenotype (28). Several studies have reported associations between EMT-related proteins and tumor metastasis and prognosis in gastric cancer (29)(30)(31). Generally, loss of epithelial proteins (such as E-cadherin and cytokeratin) and/or acquisition of mesenchymal proteins [such as b-catenin (nuclear) and N-cadherin] are associated with poor tumor differentiation, advanced stage, and poor outcome in gastric cancer (30), consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…During EMT, gastric cancer cells with fibroblastic morphologic changes show increased migration and invasiveness as a result of decreased cell-cell adhesion, and the cells then acquire a spindle-shaped, highly motile fibroblast phenotype (28). Several studies have reported associations between EMT-related proteins and tumor metastasis and prognosis in gastric cancer (29)(30)(31). Generally, loss of epithelial proteins (such as E-cadherin and cytokeratin) and/or acquisition of mesenchymal proteins [such as b-catenin (nuclear) and N-cadherin] are associated with poor tumor differentiation, advanced stage, and poor outcome in gastric cancer (30), consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (29) discovered that Twist is expressed much higher in gastric cancer tissues compared to adjacent normal tissues at mRNA and protein levels by means of RT-PCR and western blotting. Likewise, abnormal Twist expression related strongly to lower 5-year survival rates in patients of GC in the Ru et al study, yet, they emphasized that the significance disappears in cases of stage IV (30). Various examinations in vitro collaboratively implied the carciogenesis of Twist.…”
Section: Epithelial-mesenchymal Transition and Gastric Cancermentioning
confidence: 93%
“…[21][22][23] Twist expression is positively correlated with the degree of infiltration and with lymphatic and distant metastasis; in addition, cancer patients with high Twist expression exhibit lower 5-year survival rates, suggesting that Twist may be a useful marker for evaluating the prognosis of gastric cancer. 24,25 Vichalkovski examined the interaction between Twist and Akt and found that activated Akt upregulated the expression of phosphorylated Twistl and subsequently alleviated the induction of p53 caused by chemotherapy-induced DNA damage, resulting in the inhibition of apoptosis. 26 Moreover, the levels of Twist and phosphorylated Akt are also positively correlated in oral squamous cell carcinoma.…”
Section: Pi3k/akt and Transcription Factorsmentioning
confidence: 99%